2010
DOI: 10.1007/s11845-010-0594-z
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol attenuates diet-induced insulin resistance and glucose intolerance through up-regulation of caveolin-3

Abstract: Caveolin-3 plays an important role in the mechanism by which E(2) attenuates diet-induced glucose intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Insulin increases GLUT4 to plasma membrane fraction enriched by caveolae [9,38]. Our recent study has demonstrated that estrogen via its receptor improves glucose uptake by the up-regulation of CAV-3 expression in skeletal muscle cells [16]. In the present work, we showed that RSV up-regulated CAV-3 expression in HFD-induced insulin-resistant soleus muscles and in C2C12 myotubes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Insulin increases GLUT4 to plasma membrane fraction enriched by caveolae [9,38]. Our recent study has demonstrated that estrogen via its receptor improves glucose uptake by the up-regulation of CAV-3 expression in skeletal muscle cells [16]. In the present work, we showed that RSV up-regulated CAV-3 expression in HFD-induced insulin-resistant soleus muscles and in C2C12 myotubes.…”
Section: Discussionsupporting
confidence: 62%
“…More importantly, different groups have demonstrated insulin resistance in the skeletal muscle of CAV-3 knockout mice [14,15], suggesting that CVA-3 may be a critical intermediate for glucose uptake. Our previous work has also shown that estrogen via its receptor improved glucose uptake by up-regulation of CAV-3 expression in skeletal muscle cells [16]. Numerous studies have shown that RSV has molecular structure and pharmacologic properties similar to those of estradiol, so it mimics many roles of estrogen (for review, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the regulatory light chain of myosin is estradiol sensitive (16,39,44), thus providing additional evidence for estradiol's critical role in modulating myosin-actin interactions in skeletal muscle, ultimately impacting how muscle contracts and produces force. Moreover, studies on both women and female rodents show that estradiol has regulatory roles in energy metabolism and mitochondrial function, which can also affect muscle contractility (13,21,32,37,49,50,61,62). What is less clear is whether estradiol mediates its effects on contractility through estrogen receptors (ERs) or via a non-receptormediated mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Activated AKT promoted the translocation of GLUT-4 to the plasma membrane and enhanced glucose uptake. There is evidence that increased CAV-3 expression contributed to GLUT4 translocation and thus ameliorated high-fat-diet (HFD)-induced glucose intolerance and insulin resistance, which indicated a positive correlation between the alternation of glucose metabolism and the level of caveolin-3 [ 93 , 101 ]. Conversely, decreased expression levels of CAV-3 were observed in diabetes animal models [ 102 ].…”
Section: Caveolin-3 and Metabolic Perturbationmentioning
confidence: 99%